2010
DOI: 10.1111/j.1439-0310.2010.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximity‐dependent Response to Variably Complex Mating Signals in Túngara Frogs (Physalaemus pustulosus)

Abstract: The plasticity of animal behavior allows individuals to maximize fitness in a wide range of contexts. Both production of and preference for mating signals are context‐dependent according to internal factors such as hormonal state, and external factors such as predation risk. In many species, male‐to‐female proximity also defines an important context for mating communication. Males often possess short‐distance courtship signals, and females often exhibit distance‐related variation in signal response. Such varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…Akre & Ryan () also found that female túngara frogs exhibit a repertoire of movements when in close proximity to males which increase the probability that males add complexity to their calls. Interestingly, Akre & Ryan () had found that when females are ‘close’ to males (a situation modeled through increasing call intensity), a stronger preference for more chucks occurs. The results of my study open the issue of whether female preferences for call timing might influence male vocal behavior at close range.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Akre & Ryan () also found that female túngara frogs exhibit a repertoire of movements when in close proximity to males which increase the probability that males add complexity to their calls. Interestingly, Akre & Ryan () had found that when females are ‘close’ to males (a situation modeled through increasing call intensity), a stronger preference for more chucks occurs. The results of my study open the issue of whether female preferences for call timing might influence male vocal behavior at close range.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, under typical ideal experimental conditions (i.e., without conspecific interference), females prefer one, two, or more chucks over no chuck but do not discriminate between one and two chucks. Therefore, for decades, the role of multichuck whines puzzled researchers (but see recent findings in, Akre & Ryan , ; Akre et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations